Synchronization Between Local and Remote Database on The Example of The Mobile Application of The Idvictim System - Gabriel JEKATERYŃCZUK; Zbigniew PIOTROWSKI (Communications of International Proceedings, 2022)
This paper describes an approach to synchronization between the Room database of an Android system and a remote database, which is accessible with the use of the REST API. The proposed approach presents its own solution implemented in the IDVIctim system for recording the victims of disasters and terrorist attacks. The aim of the research is to introduce the used architecture and to develop a method to ensure constant synchronization between two databases in both cases, when the Internet is available and when it is not.
Keywords: Synchronization; Android; mobile development.